Peningkatan Pengetahuan Bahan Alam Untuk Kesehatan Gigi Mulut Melalui Program Merdeka Belajar Kampus Merdeka - Euis Reni Yuslianti; Rahmadaniah Khaerunnisa; Indah Puti RS; Hillda Herawati; Asih Rahaju; Dewi Lidya Ichwana; Herryawan Herryawan; Frita Ferlita SD (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2022)
It is important to improve the health of rural communities, including dental and oral health. The majority of the population of Mekarsaluyu Village, Bandung Regency, West Java, have jobs in the agricultural sector and lack knowledge of health. The global pandemic of the Covid-19 virus has lasted for two years. This condition causes people to need to make several adaptations and changes in behavior, including oral dental health. The purpose of the community service is to implement the Independent Learning Campus (MBKM) program to empower the role of students. The method of implementing this community service program is through outreach activities to the community regarding natural materials from the surrounding environment to improve oral dental health in the target villages of the Mekarsaluyu Village area and evaluated using a questionnaire to 16 respondents before and after the activity. Data were analyzed using T-test dependent (p0.05). The results of community service showed that there was an increase in knowledge after the implementation of the extension indicated by (p = 0.00). Based on the above, it can be concluded that the MBKM program plays a role in changing the knowledge of the assisted village communities.